Palladium(II)‐Catalyzed Tandem Synthesis of Acenes Using Carboxylic Acids as Traceless Directing Groups. (31st May 2016) - Kim, Kiho; Vasu, Dhananjayan; Im, Honggu; Hong, Sungwoo
Abstract: A straightforward synthetic strategy for generating useful anthracene derivatives was developed involving palladium(II)‐catalyzed tandem transformation with carboxylic acids as traceless directing groups. Carboxyl‐directed C‐H alkenylation, carboxyl‐directed secondary C‐H activation and rollover, intramolecular C−C bond formation, and decarboxylative aromatization are proposed as the key steps in the tandem reaction pathway. This novel synthetic route utilizes a broad range of substrates and provides a convenient synthetic tool that allows access to acenes.